Indian Federalism: A Study with Special Reference to S. R. Bommai v. Union of India: Examining the Impact of S. R. Bommai v. Union of India on Centre-State Relations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
S. R. Bommai v. Union of India ([1994] 2 SCR 644 AIR 1994 SC 1918 (1994)3 SCC1) was a landmark judgment of the Supreme Court of India, where the Court discussed at length provisions of Article 356 of the Constitution of India and related issues. This case had huge impact on Centre-State Relations. The judgement attempted to curb blatant misuse of Article 356 of the Constitution of India, which allowed President's rule to be imposed over state governments.